Genus und Sexus im Konflikt. : Kongruenzformen hybrider Nomina im Sprachproduktionsprozess - Hübner, Julia (Linguistik Online, 2021)
The specialty of hybrid nouns is their different agreement according to certain features of the agreement target. They result from a conflict within in the gender assignment system. For example, the German noun Mädchen (semi-transparent diminutive for denoting a girl) is grammatical neuter but it refers to a female person. In German, nouns denoting females are feminine but diminutives are neuter. Since both rules apply, you can refer to Mädchen with a neuter (es) but also with a feminine pronoun (sie).There are different factors which influence the agreement pattern: the linear distance between noun and pronoun and the type of agreement target. So far there are only few studies on the influence of possible non-grammatical factors such as the age of the referent. In this paper, I elaborate on those factors and present the results of a discourse completion task focusing on the influence of a sexualized context.